Limnological variations of a reservoir during two successive years: one wet, another dry - Geraldes, Ana Maria (2008)
Changes in environmental variables, as well as in planktonic algae and in crustacean zooplankton abundance, were investigated in a meso-eutrophic reservoir during two successive years: one wet, another dry. In the wet winter, both total phosphorus and soluble reactive phosphorus reached their maxima, whereas water transparency achieved the minimum during the same period. The obtained data suggest that total phosphorus and soluble reactive phosphorus peaks were related to the increase in nutrient loading as a consequence of the intense rainfall which occurred during this period. Phytoplankton composition was dominated by Cyclotella spp., except during the dry winter when Anabaena became dominant. The dominance of this alga seemed to be related to nitrate depletion. The establishment of more stable environmental conditions (e.g. low water turbulence, longer water retention time) and the increase of irradiance during the dry period (summer 2001 and winter 2001/2002) also favoured growth of this cyanobacterium. Concomitant to Anabaena dominance, Ceriodaphnia abundance decreased while nauplii increased. Although variation between the two years of study seemed to be related to the sequence of a pluvial and a dry year, further research is needed to evaluate whether variations in precipitation intensity influence reservoir ecological processes.